The Effect of Market Risk, Business Risk, and Financial Risk on Stock Returns in Automotive Companies - Hadiansyah Ma’sum; Budi Supriatono Purnomo; Imas Purnamasari (CV. Sakura Digital Nusantara, 2024)
This research aims to determine the influence of investment risk consisting of market risk (X1), business risk (X2), and financial risk (X3) on stock returns (Y) in automotive companies listed on the BEI in 2014-2023 simultaneously and Partial. This research data was obtained from the financial reports of automotive companies listed on the Indonesia Stock Exchange (BEI) and the finance.yahoo.com website. The research sample consisted of 10 automotive companies listed on the Indonesia Stock Exchange for 10 years, namely the 2014-2023 period. The data analysis technique used is descriptive statistical analysis and multiple linear regression analysis using the t test and F test methods. The results of the research show that the market risk variable has a significant negative influence on stock returns, business risk has a significant positive influence on stock returns and financial variables. risk has an insignificant negative effect on stock returns. Meanwhile, simultaneously (F test) the independent variables have a significant influence on the stock return variable. With a determinant coefficient (R2) of 0.111, it shows that 11.1% of the dependent variable on stock returns can be explained by independent variables consisting of market risk, business risk and financial risk and the remaining 88.9% is explained by other variables that are not researched.